1995
DOI: 10.1159/000310566
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Magnesium on Visual Field and Peripheral Vasospasm in Glaucoma

Abstract: Previous studies indicated calcium channel blockers to be of some help for normal-tension glaucoma patients. The present study evaluates the effect of magnesium, a ‘physiological calcium blocker’, in 10 glaucoma patients (6 with primary open-angle glaucoma, 4 with normal-tension glaucoma). All patients had a digital cold-induced vasospasm. Magnesium (121.5 mg) was administered twice a day for a month. After 4 weeks of treatment, the visual fields tended to improve. All three video-nailfold-capillaroscopic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…Magnesium is a physiological calcium channel blocker that partially inhibits the effect of endothelin-1 [14] and improves blood flow [13]. A dosage of 10-20 mmol daily is recommended for adults to improve the regulation of blood flow [13,99].…”
Section: Magnesiummentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium is a physiological calcium channel blocker that partially inhibits the effect of endothelin-1 [14] and improves blood flow [13]. A dosage of 10-20 mmol daily is recommended for adults to improve the regulation of blood flow [13,99].…”
Section: Magnesiummentioning
confidence: 99%
“…Magnesium is a physiological calcium channel blocker that partially inhibits the effect of endothelin-1 [14] and improves blood flow [13]. A dosage of 10-20 mmol daily is recommended for adults to improve the regulation of blood flow [13,99]. For the patient, it is important to note that the different forms of magnesium contain different amounts of magnesium, and in case they are uncertain of the correct daily dosage of the particular magnesium supplement, they should refer to their pharmacist.…”
Section: Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these could explain how magnesium may have potential therapeutic effect in some diseases associated with perfusion abnormality via local microcirculatory disturbances and decreased blood flow such as NTG. Gaspar et al [56] evaluated the effect of oral magnesium therapy in 10 glaucoma patients (6 with open angle glaucoma and 4 with NTG with normal or drug normalized IOP). All patients had a cold-induced digital vasospasm.…”
Section: Putative Therapeutic Effect In Glaucomamentioning
confidence: 99%
“…Magnesium, known as ''nature's physiological calcium blocker'' (Iseri, 1984), has also been studied regarding its impact on OBF. A small, non-randomised study has shown a statistically significant improvement in peripheral blood flow and a tendency to improve visual field scores in glaucoma patients (Gaspar, 1995). Other hypotensive medications, such as angiotensin-converting enzyme inhibitors or angiotensin receptor antagonists, have also been studied.…”
Section: Systemic Medications and Other Measuresmentioning
confidence: 99%